2019
DOI: 10.1111/jam.14252
|View full text |Cite
|
Sign up to set email alerts
|

Serratiasp.CP‐13 augments the growth of cadmium (Cd)‐stressedLinum usitatissimumL. by limited Cd uptake, enhanced nutrient acquisition and antioxidative potential

Abstract: Aims The current study was aimed to evaluate the beneficial effects and bioremediation potential of a Cd‐tolerant bacterial strain, Serratia sp. CP‐13, on the physiological and biochemical functions of Linum usitatissimum L., under Cd stress. Methods and Results The bacterial strain was isolated from the wastewater collection point of Chakera, Faisalabad, Pakistan, as this place contains industrial wastewater of the Faisalabad region. The Serratia sp. CP‐13, identified through 16S rRNA gene sequence analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 63 publications
2
7
1
Order By: Relevance
“…In general, the Cd concentration was relatively less in the aboveground and belowground tissues of E+ plants in most of the treatments ( Table 1 ). This finding was similar to the results of the previous studies that observed lower Cd in inoculated plants than non-inoculated plants ( Wang et al, 2016 ; He et al, 2017 ; Zhan et al, 2017 ; Zhu et al, 2018 ; Shahid et al, 2019 ). However, in this study, the difference was non-significant ( p > 0.05) in most of the tested conditions ( Table 1 ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In general, the Cd concentration was relatively less in the aboveground and belowground tissues of E+ plants in most of the treatments ( Table 1 ). This finding was similar to the results of the previous studies that observed lower Cd in inoculated plants than non-inoculated plants ( Wang et al, 2016 ; He et al, 2017 ; Zhan et al, 2017 ; Zhu et al, 2018 ; Shahid et al, 2019 ). However, in this study, the difference was non-significant ( p > 0.05) in most of the tested conditions ( Table 1 ).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have demonstrated that endophytes can enhance host plant growth under Cd stress ( Soleimani et al, 2010 ; Khan et al, 2015 ; Zhu et al, 2018 ; He et al, 2019 ; Shahid et al, 2019 ; Zhang et al, 2019 ). In the present study, it was found that fungal endophyte FZT214 improved D. ambrosioides growth under Cd stress.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations